MEMBRANOTROPIC EFFECT OF MONTIVIPERA RADDEI AND MACROVIPERA LEBETINA OBTUSA VENOM WITH PHOSPHOLIPASE A2 INHIBITED BY p-BROMOPHENACYL BROMIDE (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
In the article influence of Montivipera raddei and Macrovipera lebetina obtusa venom including phospholipase A2 (PLA2) inhibited by p-bromophenacyl bromide on giant unilamellar vesicles, visualized with 8-anilino-1-naphthalenesulfonic acid fluorescence probe, was investigated. The results have shown that both venoms even without the PLA2 activity have a noticeable membranotropic effect on the artificial membranes, but in different ways, so one can propose that investigated viper venoms can contain different PLA2 isomers.
Keywords: GUV, $Macrovipera~lebetina~obtuse$, $Montivipera~raddei$,phospholipase A2, p-bromophenacyl bromide